Evaluación de diferentes programas de restrícción alimenticia en pollos de carne durante el periodo de crecimiento, para reducir el sindrome ascitíco en zonas altas - Granda Bustamante, Priscilla Daniela (2019)
In the present investigation, different programs of food restriction were evaluated in chickens of meat during the growth period, to reduce the ascitic syndrome in high areas; for which, the number one shed of the Quinta Experimental Punzara of the Universidad Nacional de Loja, located at 2160 m.s.n.m. Four hundred broiler chic- kens were used, 200 males and 200 females one day old were housed in groups of 10 animals (experimental unit). The experiment was developed under a completely randomized design with factorial arrangement. For growth, two diets were elabora- ted: the first unrestricted diet was formulated based on the recommendations of the genetic line Cobb 500 (3060 Kcal/Kg y 20 % de PB), the second diet was formulated with a restriction of 10 % in energy and protein with respect to the first diet (2770 kcal/kg y 18 % de PB). Four restriction programs were tested: i) control (Without restrictions), ii) feeding the broilers with diet two from day 10 to day 20 of age, iii) restriction from day 10 to day 25 of age and iv) restriction from day 10 to day 30 of age; the diets were supplied ad libitum. The animals were sacrificed at day 42 of age (one animal per experimental unit). We weighed the total digestive tract, proventricu- lus, gizzard, small intestine and caecum. The results were analyzed, with an analysis of variance, where the main sources of variation were the restriction programs, sex and their interaction. The means were compared using a protected t-test. The qualitative restriction of day 10 to 30, improved the productive parameters, obtaining weights to the channel similar to those of the control group and reducing the mortality rate. In the digestive parameters, animals with 20-day restriction (10- 30) obtained higher weights, in organs such as: small intestine and blind causing an adequate development of the digestive tract, preparing it for the fattening stage. The effect of the food restriction did not infer the quality of the carcass of broiler chickens. The effect of the food restriction showed great efficiency in the treatments of mo- re days of restriction, obtaining a developed digestive tract, obtaining a better use of the food in the compensatory time, the restriction did not infer on the quality of the carcass. The qualitative restriction program of 10-30 days was the one that showed the best results in both productive and disgestive parameters. Key words: Ascitis, restriction, diet, treatment.